Penguatan Profesionalisme Guru Pendidikan Agama Kristen dalam Era Digital : Perspektif Etika Kristiani - Enjel Sinaga; Dorlan Naibaho (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2025)
In increasingly advanced digital era, the professionalism of Christian Religious Education (CRE) teachers has become extremely important. CRE teachers must not only possess strong academic abilities but also be prepared to face new challenges in the implementation of technology in the teaching and learning process. The Society 5.0 era demands integration between the virtual and real worlds, where advancements in information and communication technology have transformed the way education is delivered, including in CRE practices. The professionalism of CRE teachers in this era is determined by their mastery of 21st-century competencies, which include critical thinking, creativity, innovation, collaboration, and digital literacy. Therefore, CRE teachers must be able to develop innovative and engaging learning materials. This can be achieved by utilizing video tutorials, virtual simulations, and technology-based interactive games to enhance student engagement and the quality of learning. Thus, strengthening the professionalism of CRE teachers not only focuses on academic aspects but also on the application of Christian ethical values within a dynamic and digital learning environment.